Increasing Student Creativity Through the Application Of Interactive Question Development Projects Using the Construct 2 Application - Ekaputra, Firdiawan (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
The aim of this study was to investigate how using the construct 2 application to implement an interactive question development project increased student creativity. This study uses a one-group pretest-posttest design and a pre-experimental methodology. The project-based learning approach is the independent variable in this study, while student creativity is the dependent variable. The research sample consisted of 22 students who enrolled in the multimedia design course during the 2023–2024 academic year. A creativity skills questionnaire was used as the research tool. The data was subjected to a normality test both before to and following the implementation of the project-based learning approach. The hypothesis test employed in this investigation is the one sample t test. This study can be concluded that the implementation of interactive question development projects using the Construct 2 application is effective in increasing the creativity of students who take learning multimedia design courses. The project-based learning model is very beneficial in improving the skills possessed by students, especially student creativity, it is hoped that the project-based learning model can continue to be applied in learning to improve student skills